Hábitos orales, (Universidad Santiago de Cali, 2025)
The Speech Therapy Program of the Universidad Santiago de Cali, offers to the students and professionals of speech therapy the present textbook; in it they will find a series of approaches and orientations for the work of speech therapy in the specialty of orofacial myofunctional therapy. The book begins with the historical contextualization of the profession of phonoaudiology in the world, Latin America and Colombia, to later integrate the history of orofacial therapy and orofacial motricity in the same areas; at the same time it describes the beginnings.